Learning from beetles, nature's master farmers.
The sustainable production of pathogen-free crops is one of mankind's most pressing concerns, given projected population growth and the threat posed by climate change to arable land. Incredibly, the study of a species of unassuming tree-dwelling beetles could hold some answers.